2007
DOI: 10.2343/geochemj.41.391
|View full text |Cite
|
Sign up to set email alerts
|

Low total and inorganic carbon contents within the Taiwan Chelungpu fault system

Abstract: We presented the total and inorganic carbon contents of core samples recovered from the Taiwan Chelungpu fault system, which slipped at the 1999 Chi-Chi earthquake, and reported lower contents of inorganic carbon within the black gouge zone in FZB1136 (fault zone at depth 1136 m in Hole B) and in the black-material disks in FZB1194 and FZB1243.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…The following subzones were encountered in FZB1136, from top to bottom ( High magnetic susceptibilities and low inorganic carbon contents have been reported previously in the black gouge zone (Hirono et al, 2006bIkehara et al, 2007), and an intense 20-mm-thick shear zone within the black gouge zone is considered to have been the most likely slip zone during the 1999 Chi-Chi earthquake Hirono et al, 2008).…”
Section: Sample Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following subzones were encountered in FZB1136, from top to bottom ( High magnetic susceptibilities and low inorganic carbon contents have been reported previously in the black gouge zone (Hirono et al, 2006bIkehara et al, 2007), and an intense 20-mm-thick shear zone within the black gouge zone is considered to have been the most likely slip zone during the 1999 Chi-Chi earthquake Hirono et al, 2008).…”
Section: Sample Descriptionsmentioning
confidence: 99%
“…Therefore, information about temperatures in earthquake faults is important. Ikehara et al (2007) measured carbon contents in core samples from each of the three major fault zones in TCDP Hole B and reported a remarkably low inorganic carbon content in the black gouge zones within each of them. These researchers suggested that these zones had been subjected to high temperatures, because thermal decomposition of carbonate minerals occurs at temperatures above approximately 400…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive mineralogical, geochemical, and magnetic analyses of Hole B core samples have been performed, and some temperature information during the Chi-Chi earthquake has been obtained. Ikehara et al (2007) reported that the inorganic carbon content of the fault gouge was low, and attributed the low value to thermal decomposition of carbonate minerals. A chemical kinetic evaluation based on the Arrhenius equation of the thermal decomposition reaction induced by earthquake slip estimated the temperature reached in response to frictional heating during the Chi-Chi earthquake to be 868°C (Hirono et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…The black gouge zone, including the 2‐cm‐thick slip zone associated with the earthquake, has lower inorganic carbon (mainly calcite), smectite, and kaolinite contents than the surrounding zones, and its magnetic susceptibility is relatively high [ Ikehara et al , 2007; Hirono et al , 2006, 2008]. These values have been attributed to frictional heat‐induced chemical reactions, including thermal decomposition of carbonate minerals, dehydration of interlayer water of smectite, dehydroxylation of smectite, dehydroxylation of kaolinite, and the production of magnetite from thermally decomposed paramagnetic minerals such as siderite [ Ikehara et al , 2007; Hirono et al , 2008; Mishima et al , 2009]. Because these reactions are endothermic, the heat of reaction, E C , takes up energy released from the fault during the earthquake, reducing the values of other forms of energy.…”
Section: Reestimation Of Dynamic Shear Stress and Energetics During Tmentioning
confidence: 99%